The effect of the menstrual cycle on human cerebral blood flow: studies using Doppler ultrasound - Brackley, K. J.; Ramsay, M. M.; Broughton Pipkin, F.; Rubin, P. C. (Ultrasound in obstetrics & gynecology, 1999)
Objective Previous studies have demonstrated hemodynamic changes at different phases in the menstrual cycle, but the cerebral circulation has not been investigated. Our aim was to study carotid and cerebral blood flow during the menstrual cycle using Doppler ultrasound. Two different techniques of Doppler waveform analysis were used: standard Doppler indices and Laplace transform analysis (LTA), which may provide additional hemodynamic information. Design This was a prospective study of healthy volunteers who were providing pre‐conception data for a subsequent longitudinal study set in the Department of Obstetrics and Gynaecology, Nottingham University Hospital. Nineteen women were studied in the mid‐follicular and mid‐luteal phases of 27 ovulatory menstrual cycles. Doppler recordings were obtained from the internal and external carotid and middle cerebral arteries. The standard Doppler indices (systolic/diastolic ratio, pulsatility index and resistance index) and LTA parameters were calculated. Results The standard Doppler indices were all significantly higher in the luteal compared to the follicular phase in the right middle cerebral artery (p < 0.05). However, no changes were seen in the standard indices in the carotid arteries or in any of the LTA parameters in any artery. Using the LTA, vessel wall stiffness was greater and absolute velocity of flow lower in the middle cerebral compared to the carotid arteries. Conclusions Increased ventilation and a subsequent lowering of alveolar CO2 pressure secondary to a raised progesterone level in the mid‐luteal phase could account for the observed changes within the middle cerebral artery. Under the conditions of this study the LTA appears less sensitive at detecting alterations in downstream resistance compared to the standard Doppler indices. Copyright © 1999 International Society of Ultrasound in Obstetrics and Gynecology